Transnational Intellectual Property Strategies and Firms’ Knowledge Adoption: Evidence from China-U.S. Patent Dyads - HUANG, Kenneth Guang-Lih (Institutional Knowledge at Singapore Management University, 2012)
As firms increasingly operate and conduct R&D in emerging markets, 'transnational patenting' - patenting of the same invention across more than one country - is becoming a cornerstone of their intellectual property (IP) strategies. We investigate whether and how a patent granted to a focal firm's invention in an emerging economy (China) can shape its subsequent technological knowledge adoption by other firms in developed economies (U.S.). Drawing on research from market signaling and intellectual property strategy, we address this question using a novel dataset of 4,226 China-U.S. patent dyads covering 1,104 firms, and matching control sets. Difference-in-differences estimates show that patent granted to the focal firm's invention under a weak IP institution (China) increases its subsequent knowledge adoption (by up to 76%) by other firms under a strong IP institution (U.S.). The signaling effect to mitigate information asymmetry is most salient for patents awarded to China-based firms, in computing and information sector, and to technologies developed in Chinese provinces with lower de facto IP institutional quality.